2017
DOI: 10.1021/acs.joc.7b00550
|View full text |Cite
|
Sign up to set email alerts
|

Palladium Catalyzed Arylation and Benzylation of Nitroarenes Using Aryl Sulfonates and Benzyl Acetates

Abstract: Pd-catalyzed arylation or benzylation of nitroazoles using aryl sulfonates or benzyl acetates is described. Electronically varied aryl tosylates and mesylates, as well as benzyl acetates, afford the arylated and benzylated products. Arylation of nitrobenzene is also reported. The relative rate for the arylation of halides is greater than that of tosylates using the reported reaction parameters. These studies enhance the scope of electrophiles for nitroarene arylations and benzylations, which was hitherto limit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(5 citation statements)
references
References 58 publications
0
5
0
Order By: Relevance
“…These compounds can be converted into various functionalized nitroarenes via halogenation, hydroxylation, nitration, and amination processes . Although some recent research revealed that selective ortho arylation and benzylation could be achieved in the aid of Pd catalysts, regioselectivity control is always problematic and functionalized nitroarene is a minor product in most cases. Recently, Nguyen and co-workers successfully converted ortho-functionalized nitroarenes into various heterocycles (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…These compounds can be converted into various functionalized nitroarenes via halogenation, hydroxylation, nitration, and amination processes . Although some recent research revealed that selective ortho arylation and benzylation could be achieved in the aid of Pd catalysts, regioselectivity control is always problematic and functionalized nitroarene is a minor product in most cases. Recently, Nguyen and co-workers successfully converted ortho-functionalized nitroarenes into various heterocycles (Scheme b) .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, a more straightforward and general method for the reductive denitration (path B) remains highly attractive. In the chemical industry, the derivatization of fossil aromatic resources often starts with a nitration reaction, and a wide range of nitroarenes is accordingly commercially available from selective nitration reactions followed by S N Ar/S E Ar/VNS and/or ortho -selective C–H functionalization reactions, , which proceed site-selectively thanks to the strong electronic effect of the nitro group. A nitration and decoration sequence for arenes, followed by a single-step denitration reaction under mild conditions, would thus represent an efficient and practical pathway to a diverse range of functionalized arenes starting from simple arenes (Figure ).…”
mentioning
confidence: 99%
“…In addition, the concept of semicoordination of a nitro group can be applied to studies focused on revealing the finer mechanisms of metal-catalyzed and metal-mediated transformations of NO 2 -containing substrates, in particular, the understanding of the reaction directing role of the nitro group in cross-coupling. [65][66][67]…”
Section: Discussionmentioning
confidence: 99%